2016
DOI: 10.1177/1359105315580463
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of patients’ experience of living with inflammatory bowel disease: A preliminary focus on the notion of adaptation

Abstract: This study investigates the lived experience of inflammatory bowel disease with the aim of examining the process of adapting to life with inflammatory bowel disease. Adaptation is often referred to as the desirable outcome in chronic illnesses such as inflammatory bowel disease; yet little is known as to how this is achieved. A total of 10 Crohn's and 12 ulcerative colitis patients recruited from online support networks participated in individual, semi-structured interviews. The study has identified the notion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 22 publications
(21 reference statements)
3
31
0
Order By: Relevance
“…Loss of sense of self has been identified as integral to chronic disease experience generally, 31 and other researchers interested in normality in IBD have also observed that identity influences views on normality. 9 15 17 For a normal life to be achieved, the disease and its impacts have to be accommodated via adaptation, and thereby integrated into a new, and perhaps dynamic, sense of self. We did not talk to anyone with UC who described their life as being the same as before the onset of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of sense of self has been identified as integral to chronic disease experience generally, 31 and other researchers interested in normality in IBD have also observed that identity influences views on normality. 9 15 17 For a normal life to be achieved, the disease and its impacts have to be accommodated via adaptation, and thereby integrated into a new, and perhaps dynamic, sense of self. We did not talk to anyone with UC who described their life as being the same as before the onset of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel disease, the subject's not right for conversation.' (Hall et al, 2005, pg.451 (Matini andOgden, 2015, p.2497).…”
Section: Having An Invisible Illnessmentioning
confidence: 99%
“…IBD is a life-long disease and often affects young, workingaged individuals. While many studies underline the importance of adaptation in IBD patients to maintain their working capacity and quality of life, little is known about how this is achieved [22]. Many educational programs developed for IBD patients have shown no or limited effect on patient psychosocial outcomes [11,12,23].…”
Section: Discussionmentioning
confidence: 99%